Infrastructure, Development, and Vulnerability: The Uneven Effects of Rainfall on Highway Safety in Brazil - Brasileiro, Victor A. L.; Ramos, Geymerson S.; Aquino, Andre L. L. (Anais do Latin American Symposium on Digital Government (LASDiGov); 2026: Anais do XIV Latin American Symposium on Digital GovernmentDO - 10.5753/lasdigov.2026.21769, 2026)
This study presents a nationwide assessment of the association between rainfall and crash occurrence on the Brazilian federal highway network across the 27 states. The alignment between these seasonal patterns is quantified using Spearman’s correlation. The results reveal pronounced spatial variability in both the direction and magnitude of the rainfall–crash relationship. Significant negative correlations are concentrated in the North, whereas significant positive correlations are observed mainly in the Southeast and in Paraíba. A Fisher-z regression shows a positive, statistically significant association between state GDP and the strength of the correlations, indicating that more economically developed states in Brazil are more sensitive to weather-related impacts on highway safety.